Novel trastuzumab‐DM1 conjugate: Synthesis and bio‐evaluation. Issue 10 (10th March 2019) - Abedi, Mehri; Cohan, Reza Ahangari; Mahboudi, Fereidoun; Faramarzi, Mohammad Ali; Fazel, Ramin; Damavandi, Narges; Ardestani, Mehdi Shafiee; Davami, Fatemeh
Abstract: Antibody‐drug conjugates are now of considerable interest and are recommended for the treatment of cancers. Linkers are having a crucial role in potency and efficacy of these drugs. Herein, for the first time, we have used a water‐soluble poly‐ethylene glycol based linker (succinimidyl‐[( N ‐maleimido propionamido)‐diethyleneglycol] [SM(PEG)2]) for lysine amide coupling of DM1 drug to trastuzumab considering evaluation of the effect of using a hydrophilic linker on physicochemical and biological properties of the resulting conjugate in comparison to the conjugate containing succinimidyl 4‐( N ‐maleimidomethyl) cyclohexane‐1‐carboxylate (SMCC) linker, which has a relative hydrophobic nature. The physicochemical properties of synthesized conjugates were investigated in terms of drug to antibody ratio, size variants and free drug quantities. In vitro biological activity of trastuzumab‐DM1 conjugates was assessed on breast cancer cell lines expressing different levels of HER2 using binding affinity, antiproliferative, apoptosis, and antibody‐dependent cell‐mediated cytotoxicity (ADCC) assays. Synthesized conjugate containing hydrophilic linker, showed higher drug to antibody ratio, no aggregated form and higher cellular toxicity in comparison to SMCC bearing conjugate. Binding affinity and ADCC potential of conjugates was not affected upon the usage of hydrophilic linker. In conclusion, application of SM(PEG)2 for coupling of DM1 to trastuzumab enhance desirable characteristics of the resulting conjugate. Abstract : We have used a water‐soluble poly‐ethylene glycol based linker (succinimidyl‐[( N ‐maleimido propionamido)‐diethyleneglycol] [SM(PEG)2]) for lysine amide coupling of DM1 drug to trastuzumab considering evaluation of the effect of using a hydrophilic linker on physicochemical and biological properties of the resulting conjugate in comparison to the conjugate containing succinimidyl 4‐( N ‐maleimidomethyl) cyclohexane‐1‐carboxylate (SMCC) linker.